Study on Drying Shrinkage of Ternary Blended Concrete by Partial Replacement of Cement with China Clay and Fly Ash - Sai Babu, M.; Santhosh Kumar Balaji, T.; V.G.D, K. (International Journal of Engineering and Technology, 2018)
The application of residue material from the industrial operation has been the focus on waste reduction research for economic, ecological and technical reasons. The most practical way is to diminish the ecological impacts of concrete without influencing its engineering properties and to reduce the amount of cement by partial replacement with industrial wastes in concrete. A partial substitution of cement by an industrial waste in concrete is to enhance the strength and durability properties. The present experimental investigation is majorly focus on drying shrinkage of ternary concrete made by partial substitution of cement with fly ash (10%) and china clay in various proportions i.e., 10%, 20%, 30%, 40%, 50%. It is observed that the compressive strength has increased and shrinkage strain is reduced at 30% china clay and 10% fly ash replacement of cement in concrete.Â Â
Keywords: China clay (CC); Compressive strength; Drying shrinkage; Fly ash (FA); Shrinkage strains.